(3GOGH GdfahSs - (3CHh YHO Gddg GdMGQK Hf CSO GdeMGSHj, GdMGQK GdeMGSHj,J (B243 (3g` s
(3ChdgG (B:s
(3jQhi Yf HYV GdMceGA Gfg bGd GhUjc hfaSi hef SeY cdGei Jbhi Gddg GdPi Ndb GdYHGO s
(3BNQgG (B:s
(3ceG Cf GdGjeGf jRjO hjfbU hGdfGS jJaGVdhf ai GdJhcd hGdjbjf Ydi bOQ GdGjeGf s
(3Vef eLehY , JQJjHgG (B: 6s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B517s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs